EDUKASI KESEHATAN UNTUK PEREMPUAN USIA SUBUR SEBAGAI UPAYA DETEKSI DINI KANKER SERVIKS DI SIDOADI, BIRU-BIRU, DELI SERDANG - Megawati Sinambela; Meta Rosaulina; Siti Marlina (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Cervical cancer can be prevented using early detection. One method of early detection that is suitable for developing countries like Indonesia is to use the Acetic Acid Visual Inspection (IVA) method. Cervical cancer can actually be prevented using primary prevention such as increasing or intensifying outreach activities in the community by adopting a healthy lifestyle, avoiding risk factors for getting cancer. Immunization uses the Human Papillomavirus (HPV) vaccine and follows early recognition of cervical cancer by carrying out pap smears or visual pain using acetic acid (Vetricia Zach, 2018). Currently the scope of cervical cancer detection in Indonesia through pap smears and IVA is still very low low, approximately 5%, whereas the coverage of early detection is effective in inhibiting morbidity and mortality due to cervical cancer, which is 85% (Saslow, et al, 2015). IVA is a screening test for cervical cancer using 3-5% acetic acid in an inspector and can be reviewed exclusively (WHO, 2018). according to the results of the diagnostic test, IVA examination had a sensitivity of 84%, a specificity of 89%, a positive predictive value of 87%, a negative predictive value of 88. for a Pap smear examination, a sensitivity of 55%, a specificity of 90%, a positive predictive value of 84%, a negative predictive value of 69 %, from what will happen earlier, it can be concluded that the IVA examination is faster, it gives high sensitivity results (Septadina, 2015). IVA is a simple and inexpensive screening method so that cervical cancer can be detected early (Rasjidi, 2015).